Static and Dynamic Changes of Amplitude of Low-Frequency Fluctuations in Cervical Discogenic Pain - Ma, Mingyue; Zhang, Hong; Liu, Run; Liu, Hongsheng; Yang, Xiangchun; Yin, Xiaohui; Chen, Song; Wu, Xiaoping (Frontiers in Neuroscience, 2020)
Cervical discogenic pain (CDP) is a clinically common pain syndrome caused by cervical disc degeneration. A large number of studies have reported that CDP results in brain functional impairments. However, the detailed dynamic brain functional abnormalities in CDP are still unclear. In this study, using resting-state functional magnetic resonance imaging, we explored the neural basis of CDP with 40 CDP patients and 40 age-, gender-matched healthy controls to delineate the changes of the voxel-level static and dynamic amplitude of low frequency fluctuations (ALFF). We found increased static ALFF in left insula (INS) and posterior precuneus (PCu), and decreased static ALFF in left precentral/postcentral gyrus (PreCG/PoCG), thalamus (THA), and subgenual anterior cingulate cortex in CPD patients compared to healthy controls. We also found decreased dynamic ALFF in left PreCG/PoCG, right posterior middle temporal gyrus, and bilateral THA. Moreover, we found that static ALFF in left PreCG/PoCG and dynamic ALFF in THA were significantly negatively correlated with visual analog scale and disease duration, respectively. Our findings provide the neurophysiological basis for CDP and facilitate understanding the neuropathology of CDP.